Janus Kinase Mediates Faster Recovery From Sevoflurane Anesthesia Than Isoflurane Anesthesia in the Migratory Locusts - Ma, Zongyuan; Zheng, Jialin C.; Li, Tianzuo; Xie, Zhongcong; Kang, Le (Frontiers in Physiology, 2022)
Inhalation anesthetics isoflurane and sevoflurane have been widely used in clinical practice for anesthesia. However, the molecular mechanisms underlying the faster recovery from sevoflurane anesthesia than isoflurane anesthesia remain largely undetermined. Herein, we use RNA-seq, RNA interference, quantitative real-time PCR and western blotting to explore the mechanisms of recovery from isoflurane and sevoflurane anesthesia in the migratory locusts. Although the migratory locusts show similar anesthetic responses to these two chemicals in corresponding half-maximal effective concentrations (EC50s), the recovery from sevoflurane anesthesia is significantly faster than that for isoflurane anesthesia after 30 min of anesthetic exposure. Transcriptome analysis shows that those transcripts involved in cytoskeletal components, Janus kinase (JAK) pathway and cuticle protein are differentially expressed in locust brains in response to isoflurane and sevoflurane . RNAi knockdown confirms that Actin, Myosin-like protein 84B (Mlp84B), JAK and cuticle protein NCP56 do not affect anesthetic response of the locusts to these two chemical anesthetics. Moreover, actin, Mlp84B and NCP56 do not affect differential recovery from isoflurane and sevoflurane anesthesia, whereas RNAi knockdown of JAK and its partner STAT5B does not affect anesthetic recovery from isoflurane but elongates recovery duration from sevoflurane anesthesia. Thus, JAK may mediate faster recovery from sevoflurane anesthesia than from isoflurane anesthesia in the migratory locust. This finding provides novel insights into the molecular mechanism underlying faster recovery from sevoflurane anesthesia than isoflurane anesthesia.